Antibacterial Activity Test of Anti-Acne Gel Preparations Containing Ethanol Extracts of Bidara Arab Leaf (Ziziphus spina-christi (L.) Desf) Againts Propionibacterium acnes - Muzayyidah; Asri SR, Muhammad; Riska Safitri (CV. Nusantara Scientific Medical, 2023)
Bidara arab leaf (Ziziphus spina-christi (L.) Desf) is one of the plants that have the potential as an anti-acne. The content of secondary metabolites contained in bidara arab leaves include alkaloids, polyphenols, flavonoids, saponins, and tannins. These secondary metabolites can inhibit the growth of acne causing bacteria, namely Propionibacterium acnes. The purpose of this study was to create a good gel dosage form of the ethanol extract of bidara arab leaves and to test the antibacterial activity of the gel formulation against Propionibacterium acne. This research method was carried out experimentally on a laboratory scale, namely ethanol extract of bidara arab leaves made in the form of anti-acne gel preparations with several concentration, including F1(1%), F2 (3%), and F3 (5%). Then proceed with the evaluation of the preparation with organoleptic test, homogenity test, pH test, adhesion test, and dispersion test. Anti-acne gel preparations had antibacterial activity based on a concentration of 1% of 12.46 mm (strong), 3% of 13.66 mm (strong), and 5% of 14.71 mm (strong), negative control had no inhibition zone and positive control 20.92 mm (very strong). strong) So, it can be included that the formulation of anti-acne gel preparations able to inhibit the growth of Propionibacterium acnes.